The Matching Process: Search or Mismatch? - Nils Gottfries; Karolina Stadin (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine the matching process using monthly panel data for local labour markets in Sweden. We find that an increase in the number of vacancies has a weak effect on the number of unemployed workers being hired: unemployed workers appear to be unable to compete for many available jobs. Vacancies are filled quickly and there is no (or only weak) evidence that high unemployment makes it easier to fill vacancies; hiring appears to be determined by labour demand while frictions and labour supply play small roles. These results indicate persistent mismatch in the labour market.
Keywords: J23; J62; J63; J64; 330; structural unemployment; frictional unemployment; matching function; labour demand; labour supply